2017
DOI: 10.1016/j.radonc.2016.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric parameters correlate with duodenal histopathologic damage after stereotactic body radiotherapy for pancreatic cancer: Secondary analysis of a prospective clinical trial

Abstract: Purpose Prospectively assess relationships between dosimetric parameters and histopathologic/clinical duodenal toxicities in patients on a phase I trial for pancreatic cancer. Methods Forty-six borderline resectable/unresectable patients were enrolled on a prospective trial testing neoadjuvant gemcitabine/5-fluorouracil followed by SBRT (5 daily fractions of 5–8 Gy) and concurrent nelfinavir. Post-SBRT surgery was performed in 13 resectable patients, which constituted the patient population herein. Pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Our study showed that duodenal histologic damage correlates with mean duodenal dose, V20–V35, and PTV mean/maximum doses [328]. As the use of high-dose SBRT regimens becomes widespread, it is imperative to explore modalities that can selectively radioprotect adjacent organs without altering the tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that duodenal histologic damage correlates with mean duodenal dose, V20–V35, and PTV mean/maximum doses [328]. As the use of high-dose SBRT regimens becomes widespread, it is imperative to explore modalities that can selectively radioprotect adjacent organs without altering the tumor response.…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that duodenal histologic damage but not the clinical toxicities correlate with the mean duodenal dose, V20-V35, and the PTV mean/maximum doses. In this cohort, four grade-2 and one grade-3 acute toxicities were observed (18).…”
Section: Discussionmentioning
confidence: 73%
“…Published data on OAR constraints and toxicity show a large heterogeneity. For pancreatic cancer Kelly described a correlation of V 55Gy within the duodenum and gastro-intestinal toxicity [23], however in a small cohort of patients treated with hypofractionated stereotactic RT duodenal DVHs only correlated to histomorphological alterations but not to clinical scored toxicity [24]. The best available data on small intestine constraints from QUANTEC recommends that the dose to the small bowel receiving ≥ 45 Gy should not exceed 200 ml, if the entire peritoneal space is delineated.…”
Section: Discussionmentioning
confidence: 99%